(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Cardiac valve disorders are one of the leading causes of heart disease and can significantly affect the function of the heart. The diagnosis and conservative treatment of cardiac valve defects involve a comprehensive approach, including clinical evaluation, imaging techniques, and pharmacological interventions. The most common types of valve disorders include stenosis and regurgitation, which may affect the aortic, mitral, tricuspid, and pulmonary valves. Timely diagnosis and conservative management, such as the use of medications to alleviate symptoms and prevent complications, play a crucial role in improving the quality of life of affected patients. This study explores diagnostic methods, including echocardiography and auscultation, as well as conservative treatment strategies aimed at controlling symptoms and preventing disease progression.